Social representation of military profession and military actions / Reprezentarea socială a profesiei de militar și a acțiunilor militare - MELENTIEVA Aliona (EcoSoEn: Ştiinţe Economice, Sociale şi Inginereşti = Economics, Social and Engineering Sciences)
The research of social representation allow as to shape the social reality of a variety of phenomena, values, objects, etc., and everything around us through the collectiveindividualistic view of society members. At present time, the topic of war has a primary actuality worldwide taking into consideration military actions that take place in Ukraine. The research was started before the military actions initiated by Russian Federation on Ukrainian territory, and continued after – February-April 2022. We would like to mention that the given situation marked as well the results of our research, taking into account the fact that our main topic is military field. In this order of ideas, we researched the social representation of military profession and social representation of military actions. The subjects involved in research are employers with active military status.